Analisis Penggunaan Alat Pelindung Diri Terhadap Status Kesehatan Petani Penyemprot Pestisida - Mayang Dwi Octavia; Susilawati, Susilawati (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
Farmers who use pesticides incorrectly can experience health problems because direct contact with pesticides can cause acute and chronic poisoning. Many farmers have not fully complied with the use of PPE, which has resulted in serious incidents to their health status. This research study is a literature review, by extracting all research that includes the use of personal protective equipment on the health status of pesticide spraying farmers. The results of the analysis show that farmers must learn about pesticides, because by learning farmers will know and have knowledge about pesticides to be able to carry out pesticide management in the recommended way, so that the risk of poisoning can be avoided and overcome. Working with pesticides for a long time can lead to higher risk factors for the accumulation of toxins in the body and will eventually lead to chronic poisoning. With the age of the 50-year-old pesticide spraying farmer, the risk of pesticide poisoning has the potential to occur. Farmers who do not use PPE will experience a decrease in health status in work productivity. Farmers who have knowledge about the dangers and risks of pesticides that will arise if they do not use PPE completely and correctly can prevent poisoning and chronic disease due to exposure due to longer work and exposure to pesticides.